Genetic Variability and Correlations of a Few Quantitative Characters in the Pasture Grass, Cenchrus ciliaris - Yadav, M. S.; Mehra, K. L.; Magoon, M. L. (Indian Forester, 1974)
Heritability, genetic advance and correlations among nine characters were analysed in twentyeight varieties of the pasture grass, Cenchrus ciliais. The differences among the varietal means of all characters were significant. The genotypic and phenotypic coefficients of variability were moderate for some characters and low for the others. The heritability and genetic advance of the characters studied ranged from 39.13 to 97.12 and 17.056 to 51.11 percent, respectively. The leaf number, leaf breadth and involucel number showed high heruitability and high genetic advance, indicating that straight selection is likely to improve them. The genotypic correlation coefficients were higher than the phenotypic correlation coefficients for most of the character combinations studied. The plant height, leaf breadth, spike length and fodder yield were significantly and positively correlated with each others, in all combinations, at the genotypic and phenotypic levels. The results suggested that the breeder should select, tall plants bearing broad leaves and long spikes havlng many involucels to develop high fodder and seed (involucel) yielding types of C. ciliaris.